Immobilization of Humic Acid on Chitosan and Its Application as an Adsorbent for Mercury (Hg²⁺) Ions in Freshwater Media - Uktolseya, Lady Diana; Male, Yusthinus T; Tehubijuluw, Hellna (Jurnal Kimia Fullerene, 2026)
Mercury (Hg²⁺) contamination in freshwater is a serious global environmental issue, posing toxic effects on both human health and aquatic ecosystems. This study aims to immobilize humic acid onto chitosan and evaluate its effectiveness as an adsorbent for mercury ions (Hg²⁺) in a freshwater medium. Humic acid was isolated from peat soil and characterized using Fourier Transform Infrared (FTIR) Spectroscopy. Commercial chitosan was used as the supporting matrix. The immobilization process was carried out by mixing humic acid and chitosan solutions under controlled pH conditions. The resulting humic acid–chitosan adsorbent was then tested for its adsorption capacity toward mercury ions at various initial concentrations. FTIR characterization results confirmed the successful immobilization of humic acid onto chitosan, as indicated by the appearance of characteristic absorption bands corresponding to functional groups from both components. Adsorption tests showed that the humic acid–chitosan adsorbent exhibited a significant ability to remove mercury ions from freshwater, with optimum adsorption observed at a concentration of 100 ppm. The maximum adsorption capacities of humic acid, chitosan, and humic acid–chitosan were 99.83 mg/g, 99.90 mg/g, and 99.89 mg/g, respectively. This study provides important scientific insights into the potential of humic acid immobilized on chitosan as an alternative material for reducing heavy metal pollution in aquatic environments